Determining the global citizenship tendencies of international university students for a sustainable world - Adem Uzun; Osman Akhan; Saim Turan; Ali Özkaya (PLoS ONE, 2025)
This study examines the relationship between the global citizenship awareness of international students studying at universities in Turkey and their orientation toward sustainability. While global citizenship and sustainability have often been explored separately in the literature, the way international students connect these two concepts has not been sufficiently addressed. Therefore, this study aims to fill this gap. A convergent parallel mixed-methods design was employed. Quantitative data were collected from 634 international students (323 women, 311 men) enrolled at four Turkish universities using the Global Citizenship Scale. Qualitative data were gathered through face-to-face interviews with 37 volunteer students. Quantitative findings indicated a moderate level of global citizenship awareness among students. In contrast, qualitative results revealed a more nuanced and higher level of awareness, with students demonstrating the ability to interpret global citizenship from multiple perspectives. Both sets of findings suggest that students develop awareness of environmental and social issues, that active participation enhances their global citizenship awareness, and that they adopt sustainable living practices (e.g., sustainable consumption, resource management). Furthermore, many participants reported applying global citizenship principles in their daily lives. These findings suggest that international students can play a significant role in promoting sustainability and global awareness. The study highlights the importance of integrating global citizenship and sustainability education into higher education curricula to strengthen students’ roles as agents of sustainable change.